High‐Intensity Laser Triggered Proton Acceleration from Ultrathin Foils. Issue 2 (31st January 2013) - Brantov, A.; Bychenkov, V. Yu.; Romanov, D. V.; Dollar, F.; Maksimchuk, A.; Krushelnick, K.
Abstract The recently developed PIC code MANDOR features arbitrary target design including 3D preplasma and the 6‐component laser fields of a tightly focused laser beam. The 3D simulations have been performed to model recent HERCULES experiments on proton acceleration, where protons with energy greater than 20 MeV were produced using just 1.5 J laser pulses focused to intensity of 2 × 1021 W/cm2. By adapting the 3D target geometry relating to ps‐prepulse effect, reasonable agreement with experimental data for the proton energy spectrum has been achieved. The effect of the 3D preplasma shape on efficiency of proton acceleration is discussed. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)